Karakteristik Akta Otentik Pada Akta Risalah Lelang - Mohamad Erik; Triyanto Triyanto; Rusdiyanto Sesung (Jatiswara, 2018)
Notary Public Officer has the duty to make an authentic deed and dare to make the deed of minutes of auction. One of the hallmark of the Auction of Minutes of Deed is made by the Auction Officer appointed by the Minister of Finance. The strength of the proof consists of the power of proof of birth, formal and material relationships has been regulated in Article 1868 of the Civil Code. Is the Deed of Minutes auction referred to the Authentic Deed. Make the form of the deed determined by law. The result of this thesis research is the status of the Auction of Minutes of the Auction referred to as the authentication deed because (1) the form of the authentic deed is the drafting of the law (Articles 37, 38 and 39 Vendu Reglement, (2) the original deed must be made by or against the general officials The auction is made by the auction official (3) of what authority, when and where the deed was made. (Articles 3 and 7 Vendu Reglement) is determined by the Minister of Finance. The Power of Evidence On The Deed of Auction Minutes As an authentic deed, In Article 35 of the Vendu Reglement from which "From every public sale by the Auction Officer or his proxy, during the sale, for each day of auction or sale shall be made separate news event". Here it is clear that the Auction Risks must be made by an authentic deed, as the auction treatise has a perfect proof of power on what is contained therein.